Study Of Water Quality In Sungai Kereh: Analysis On The Effluent Discharged From Kampung Selamat Based On The Requirement Standard - Zaiful Bahari, Siti Khairina (Universiti Sains Malaysia, 2022)
Sungai Kereh that is located in Tasek Gelugor, Pulau Pinang has been classified aspolluted with “Class V” and the issue is caused by the pig farming activities in Kampung Selamat. The effluent from the pig farming activities is flushed to the man-made drainknown as Parit Cina that carry the effluent straight to the Sungai Kereh. The issue has been unsettled for 40 years already and has disturbed the residents who lives nearby tohave a good life quality due to the bad odours. Therefore, study on this issue has been made through effluent assessment quality from each farms and to observe how every parameters related to each other. Pig farming activities that include food waste, urine, faeces and manure will result on ammonia production that are found in effluent. High amount concentration of ammonia that is indicated by parameter of ammoniacal nitrogen can affect the water quality in manyways. It can affect other parameters too such as the pH, dissolved oxygen, biochemical oxygen demand (BOD), chemical oxygen demand (COD) and total suspended solid. Theconcentration has been fixed its limit based on the requirement effluent standard. As for that, analysis on the stated parameters are done for both in-situ and laboratory test. Fromthis analysis, what can be concluded is that all of the parameters value are related to each other. The analysis also provides information based on the results obtained from the sample to determine which effluent pig farms cause the major pollutants. Moreover, house system done for pig farming activities might as well be the factor that can influencethe pollution for this issue especially on the odors production.